2017
DOI: 10.1093/ckj/sfx026
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent reference intervals for estimated and measured glomerular filtration rate

Abstract: BackgroundDefining mean and reference intervals for glomerular filtration rate (GFR) has been the subject of only a limited number of studies and review articles, with contradicting statements about the mean. Normal measured GFR (mGFR) values of ∼120–130 mL/min/1.73 m2 have long been the referenced values for young adults but seem to be too high according to recent studies. Reference intervals are difficult to define because of the age decline of GFR, which is also observed in healthy subjects. Little data are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 29 publications
(42 reference statements)
6
65
1
Order By: Relevance
“…In the AKX program, in addition to require an uncorrected mGFR ≥80 ml/min for donor candidates to be accepted, the program strictly excludes patients with urinary protein/creatinine ratio >20 mg/mmol, age ≥70 years, BMI >35 kg/m 2 , diabetes mellitus, treated hypertension requiring >2 agents to control, which differs from the risk-profile of the general donor population in Australia [35], and, consequently, our data may not be sufficiently generalizable. Nevertheless, in relation to age and GFR our cohort is similar to many other previously studied cohorts of healthy individuals [36][37][38]. In conclusion, data from the Australian KPD living donor cohort, selected based on a raw mGFR of at least 80 ml/min, demonstrates that kidney donation has acceptable short-term functional consequences, even for donors with low predonation eGFR (<80 ml/ min/1.73 m 2 ), with 75% of donors showing a drop of ≤35% in postdonation eGFR compared with predonation and 70% having an eGFR ≥60 ml/min/1.73 m 2 at 1-year postdonation.…”
Section: Discussionsupporting
confidence: 80%
“…In the AKX program, in addition to require an uncorrected mGFR ≥80 ml/min for donor candidates to be accepted, the program strictly excludes patients with urinary protein/creatinine ratio >20 mg/mmol, age ≥70 years, BMI >35 kg/m 2 , diabetes mellitus, treated hypertension requiring >2 agents to control, which differs from the risk-profile of the general donor population in Australia [35], and, consequently, our data may not be sufficiently generalizable. Nevertheless, in relation to age and GFR our cohort is similar to many other previously studied cohorts of healthy individuals [36][37][38]. In conclusion, data from the Australian KPD living donor cohort, selected based on a raw mGFR of at least 80 ml/min, demonstrates that kidney donation has acceptable short-term functional consequences, even for donors with low predonation eGFR (<80 ml/ min/1.73 m 2 ), with 75% of donors showing a drop of ≤35% in postdonation eGFR compared with predonation and 70% having an eGFR ≥60 ml/min/1.73 m 2 at 1-year postdonation.…”
Section: Discussionsupporting
confidence: 80%
“…Figure 2 demonstrates that percentiles of normal GFR in healthy African subjects matched with those in Whites, both in Ivory Coast and in the Democratic Republic of Congo (DRC). 18,26…”
Section: Percentiles Of Normal Mgfrmentioning
confidence: 99%
“…Pottel et al reported that GFR measured by gold standard method had decreasing trend in GFR with increasing age. He also reported lower GFR in older females compared to matched males.…”
Section: Discussionmentioning
confidence: 99%